Evaluating EndoC βH5 pseudoislets as a model for human islet transplantation - Lydia F. Daniels Gatward; William T. Blackstone Whines; Tzu‐Wen Hong; Rosie Sullivan; Jessica Starikova; Adya Lonsane; Ryea Arora; Victoria Salem; Min Zhao; Peter M. Jones; Aileen F. J. King; Shanta J. Persaud (Diabetic Medicine, 2026)
Abstract Aims The EndoC βH5 cell line represents a promising human β‐cell model for preclinical diabetes research. Indeed, EndoC βH5 cells aggregate into islet‐like organoids, secrete insulin in a glucose‐dependent manner, and express a variety of β‐cell functional markers. However, EndoC βH5 cell survival and functionality in vivo have not yet been investigated. Here, we have transplanted EndoC βH5 pseudoislets under the kidney capsule in SCID mice and analysed their capacity to regulate whole body blood glucose concentrations. Methods EndoC βH5 pseudoislets were formed in agar microwells. Oxygen consumption rate and glucose‐stimulated insulin secretion were quantified in vitro. After 31 days, groups of 1000 EndoC βH5 pseudoislets were transplanted under the kidney capsule in SCID mice. To selectively ablate endogenous β‐cells, streptozotocin was administered 1 month after transplantation, and EndoC βH5 graft function was analysed through quantification of blood glucose and human plasma insulin. Results EndoC βH5 pseudoislets exhibited glucose‐induced insulin secretion at 15 days, which was maintained at 31 days of culture. Human insulin was detectable in mouse plasma at 1 week post‐transplantation. Despite this, streptozotocin administration led to overt diabetes in transplant recipients. Conclusion EndoC βH5 pseudoislets secrete insulin in a glucose‐responsive manner in vitro, remain viable in vivo, and secrete insulin. Despite this, transplantation of 1000 pseudoislets is not sufficient to maintain glycaemia when endogenous β‐cells are destroyed. Nonetheless, EndoC βH5 pseudoislets represent a useful tool for preclinical islet transplantation studies where graft control of systemic glycaemia is not a requirement.